Question and Answers Forum

All Questions      Topic List

Trigonometry Questions

Previous in All Question      Next in All Question      

Previous in Trigonometry      Next in Trigonometry      

Question Number 10955 by Joel576 last updated on 04/Mar/17

If  ((cos θ)/(1 − sin θ)) = a           a ≠ (π/2) + 2kπ  So,  tan (θ/2) = ...  (A)  (a/(a + 1))                 (D)  ((a + 1)/(a − 1))  (B)  (1/(a + 1))                  (E)  (a/(a − 1))  (C)  ((a − 1)/(a + 1))

Ifcosθ1sinθ=aaπ2+2kπSo,tanθ2=...(A)aa+1(D)a+1a1(B)1a+1(E)aa1(C)a1a+1

Answered by ajfour last updated on 04/Mar/17

  ((sin ((π/2)−θ))/(1−cos ((π/2)−θ)))=((2sin ((π/4)−(θ/2))cos((π/4)−(θ/2)) )/(2sin^2 ((π/4)−(θ/2))))  =cot ((π/4)−(θ/2)) = a  tan ((π/4)−(θ/2)) =(1/a)  ; let tan ((θ/2))= p  ((1−p)/(1+p)) =(1/a) ⇒ a−ap =1+p  p =((a−1)/(a+1)) .

sin(π2θ)1cos(π2θ)=2sin(π4θ2)cos(π4θ2)2sin2(π4θ2)=cot(π4θ2)=atan(π4θ2)=1a;lettan(θ2)=p1p1+p=1aaap=1+pp=a1a+1.

Commented by Joel576 last updated on 05/Mar/17

thank you very much

thankyouverymuch

Answered by ridwan balatif last updated on 04/Mar/17

another way  (((cosθ)/(1−sinθ)))^2 =(a)^2   ((cos^2 θ)/((1−sinθ)^2 ))=a^2   (((1−sin^2 θ))/((1−sinθ)^2 ))=a^2   (((1−sinθ)(1+sinθ))/((1−sinθ)(1−sinθ)))=a^2   ((1+sinθ)/(1−sinθ))=a^2   sinθ=((a^2 −1)/(a^2 +1))  cosθ=((2a)/(a^2 +1))  remember: tan(θ/2)=((sinθ)/(1+cosθ))  tan(θ/2)=(((a^2 −1)/(a^2 +1))/(1+((2a)/(a^2 +1))))  tan(θ/2)=(((a^2 −1)/(a^2 +1))/(((a^2 +2a+1)/(a^2 +1))  ))  tan(θ/2)=((a^2 −1)/(a^2 +2a+1))  tan(θ/2)=(((a−1)(a+1))/((a+1)^2 ))  tan(θ/2)=((a−1)/(a+1))  Answer: (C)

anotherway(cosθ1sinθ)2=(a)2cos2θ(1sinθ)2=a2(1sin2θ)(1sinθ)2=a2(1sinθ)(1+sinθ)(1sinθ)(1sinθ)=a21+sinθ1sinθ=a2sinθ=a21a2+1cosθ=2aa2+1remember:tanθ2=sinθ1+cosθtanθ2=a21a2+11+2aa2+1tanθ2=a21a2+1a2+2a+1a2+1tanθ2=a21a2+2a+1tanθ2=(a1)(a+1)(a+1)2tanθ2=a1a+1Answer:(C)

Commented by Joel576 last updated on 05/Mar/17

thank you very much

thankyouverymuch

Terms of Service

Privacy Policy

Contact: info@tinkutara.com